Transatlantic Central Europe : Contesting Geography and Redifining Culture beyond the Nation - Labov, Jessie (Book collections on Project MUSE., 2019)
The concept of Central Europe has receded as a political and intellectual project, and the term has lost most of the weight it had in the 1980s and early 1990s. Proponents of a distinct cultural profile of this group of countries all now involved in the process of Transatlantic integration used Central European as an alternative for the geo-political label of Eastern Europe. This book discusses the transnational set of practices connecting journals with other media in the mid-1980s that disseminated the idea of Central Europe simultaneously in East and West.